Про методи подавлення широкосмугового шуму в звукових сигналах - Григор'єв, В. Г. (My University, 2018)
This paper analyzes some of the methods and devises of noise reduction in sound signals. It is consider additive stationary noise. Into this group can be fits many smooth and time-homogeneous noise, such as tape noise, microphone preamplifier noise, noise of ventilation in the recording studio. The features of the algoritm application of noise gate, dynaural noise suppressor, multiband gate and spectral subtraction method is consider. The advantages and disadvantages of these algorithms for noise reduction is analyse. As a result draw conclusion about the prospects of spectral subtraction algorithm.
Keywords: широкосмуговий сигнал; звуковий сигнал